Implementasi Permainan Tradisional Goboy sebagai Meningkatkan Minat Belajar Siswa dalam Pembelajaran PJOK SMA Negeri 14 Surabaya - A. Aulia Firda Mahanta; Bambang Ferianto Tjahyo Kuntjoro; Ririn Dwitjahjono (Student Research Journal, 2024)
This research aims to overcome the problem of low interest in studying in class XI students at SMA Negeri 14 Surabaya through the innovative application of the traditional game Goboy. This research lasted for three months and involved 30 students as research subjects. Research data was obtained through observation, interviews and documentation. The research results show a significant increase in students' interest in learning, especially in the aspects of active participation and enthusiasm in participating in learning. However, there were several obstacles faced during the research, such as limited time and facilities